Contributions of biofilm-induced flow heterogeneities to solute retention and anomalous transport features in porous media. (1st February 2022) - Perez, Lazaro J.; Parashar, Rishi; Plymale, Andrew; Scheibe, Timothy D.
Highlights: We integrate experimental biofilm images of Paenibacillus 300A strain with mathematical modeling. Bioflm is represented as a synthetic porous structure with physical properties varying locally. Biofilm enhances anomalous solute transport by inducing long trapping events of solute particles. When biofilm is present the pore structure becomes more spatially correlated. Breakthrough curves exhibit extreme anomalous slope and very marked late solute arrival due to solute retention. Abstract: Microbial biofilms are ubiquitous within porous media and the dynamics of their growth influence surface and subsurface flow patterns which impacts the physical properties of porous media and large-scale transport of solutes. A two-dimensional pore-scale numerical model was used to evaluate the impact of biofilm-induced flow heterogeneities on conservative transport. Our study integrates experimental biofilm images of Paenibacillus 300A strain in a microfluidic device packed with cylindrical grains in a hexagonal distribution, with mathematical modeling. Biofilm is represented as a synthetic porous structure with locally varying physical properties that honors the impact of biofilm on the porous medium. We find that biofilm plays a major role in shaping the observed conservative transport dynamics by enhancing anomalous characteristics. More specifically, when biofilm is present, the pore structure in our geometry becomes more spatially correlated. We observe intermittent behavior in the Lagrangian velocities that switches between fast transport periods and long trapping events. Our results suggest that intermittency enhances solute spreading in breakthrough curves which exhibit extreme anomalous slope at intermediate times and very marked late solute arrival due to solute retention. The efficiency of solute retention by the biofilm is controlled by a transport regime which can extend the tailing in the concentration breakthrough curves. These results indicate that solute retention by the biofilm exerts a strong control on conservative solute transport at pore-scale, a role that to date has not received enough attention.